2018
DOI: 10.1111/apps.12142
|View full text |Cite
|
Sign up to set email alerts
|

Another Test of Gender Differences in Assignments to Precarious Leadership Positions: Examining the Moderating Role of Ambivalent Sexism

Abstract: Women face significant hurdles in the attainment of leadership positions. When they do attain them such positions tend to be riskier than those attained by men, a form of bias called glass cliff. This study investigates ambivalent sexism as an individual difference that influences the occurrence of glass cliff. Little research examines individual differences contributing to glass cliff. It is proposed that individuals with high hostile and benevolent sexism are more likely to perceive women to be suitable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 97 publications
(158 reference statements)
1
24
0
Order By: Relevance
“…By investigating variations in crisis typology, our findings add to explanations for the glass cliff. Specifically, beyond extending past research that has identified motivating factors for the glass cliff which do not value women’s or communal competences [ 13 , 63 ], we investigated crisis contexts where stereotypically feminine qualities are perceived as an added value for leadership effectiveness. Although the mechanism explaining the think crisis-think feminine association has been understood in the present research, the underpinnings of the think crisis-think female association are more complex.…”
Section: Discussionmentioning
confidence: 99%
“…By investigating variations in crisis typology, our findings add to explanations for the glass cliff. Specifically, beyond extending past research that has identified motivating factors for the glass cliff which do not value women’s or communal competences [ 13 , 63 ], we investigated crisis contexts where stereotypically feminine qualities are perceived as an added value for leadership effectiveness. Although the mechanism explaining the think crisis-think feminine association has been understood in the present research, the underpinnings of the think crisis-think female association are more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In the hostile case, the strong activation of this stereotype can reinforce a “think manager-think male” association ( Schein, 1973 ), leading to decisions that protect the male image in defense of the stereotype. Disproportionate pairing of women with leadership assignments where failure is imminent also tends to reinforce traditional divisions in gender roles, where men are assumed to be competent in leadership capacities and women are not ( Acar & Sümer, 2018 ; Cook & Glass, 2014 ; Rink et al, 2013 ; Ryan et al, 2011 ).…”
Section: Multiple Motives For Glass Cliffsmentioning
confidence: 99%
“…Furthermore, when women are promoted to senior leadership, authors highlight the benevolent sexism that exists. The 'glass cliff' phenomena is frequently used to explain how women are set up to fail-they experience shorter than average tenures, thereby receiving less opportunity than men to prove their leadership capability (Cook and Glass 2014;Jenter and Kanaan 2015), women are more likely to be promoted to precarious positions in poorly performing organizations (Ryan et al 2016;Elsaid and Ursel 2018;Bruckmüller et al 2014;Acar and Sümer 2018), and women are terminated more frequently when they subsequently follow someone else's bad leadership (Kulich et al 2015) than men.…”
Section: Women In Indonesia's Public Service Echelonsmentioning
confidence: 99%